Giant chylolymphatic mesenteric cyst and its successful enucleation: A case report - Al Booq, Yousuf (Elsevier, 2014)
INTRODUCTION: Cysts of the mesentery are among surgical rarities. The clinical presentation is not characteristic and in addition, the preoperative imaging although suggestive is not diagnostic in this case ultrasound and CTscan was consistent with giant mesenteric cyst. In most cases, the diagnosis is confirmed after surgical exploration. PRESENTATION OF CASE: A 42 yrs old male patient on exploratory laparotomy had a 14cm×10cm×10 cm cysts which was seen arising from the mesentery ofdistal jejunum 80cm from the duodeno jejunal flexure. The cyst was enucleated successfully from themesentery without entailing resection. The cyst contained milky white fluid consistent with a chylolymphatic cyst. The diagnosis was confirmed on histopathology which revealed a cyst wall with lymphoidaggregates. After 3 years of follow-up, the patient is doing well and there is no evidence of recurrence. DISCUSSION: The cysts may be asymptomatic or maymanifest with abdominal pain, distension lump or intestinal obstruction. Our patient was symptomatic with mild and long standing abdominal pain. The definitive diagnosis of these lesions is difficult prior to surgical exploration as there are no pathognomonic symptoms or characteristic imaging findings. CONCLUSION: Cysts of the mesentery are among surgical rarities. In most of the cases the diagnosis is confirmed after surgical exploration and removal of thecyst. We would like to emphasize the importance of successful enucleation of the cyst irrespective of its size due to its independent blood supply as opposed to enterogenous cyst which requires bowel resection and anastomosis.